Paradise city : a novel of suspense - Carcaterra, Lorenzo (New York : Ballantine Books, 2005)
When his niece mysteriously vanishes in New York City, Giancarlo Lo Manto, a Naples police inspector, arranges for a temporary assignment to the NYPD, joining forces with Manhattan veteran Jennifer Fabini to search for the missing girl.
National College of Business and Arts
Keywords: Missing persons -- Fiction; Suspense fiction